2016
DOI: 10.1097/md.0000000000004157
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment glucose status determines HCC development in HCV patients with mild liver disease after curative antiviral therapy

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…Previous studies [62][63][64] conducted on IFN-treated patients showed that viral eradication resulted in a significant reduction in liver-related events (hepatic decompensation, variceal bleeding, HCC) in cirrhotic patients. Similarly, two studies [65,66] on noncirrhotic HCV-positive patients with IFN-induced SVR demonstrated a decrease in the incidence of HCC. However, much evidence [63][64][65][66][67][68][69][70][71][72] suggests that DM is an independent predictor of HCC, despite viral eradication obtained by IFN-based therapies.…”
Section: What Is the Clinical Impact Of Daa-induced Svr On The Incidementioning
confidence: 87%
“…Previous studies [62][63][64] conducted on IFN-treated patients showed that viral eradication resulted in a significant reduction in liver-related events (hepatic decompensation, variceal bleeding, HCC) in cirrhotic patients. Similarly, two studies [65,66] on noncirrhotic HCV-positive patients with IFN-induced SVR demonstrated a decrease in the incidence of HCC. However, much evidence [63][64][65][66][67][68][69][70][71][72] suggests that DM is an independent predictor of HCC, despite viral eradication obtained by IFN-based therapies.…”
Section: What Is the Clinical Impact Of Daa-induced Svr On The Incidementioning
confidence: 87%
“…Several factors have been predictive of HCC in the post-SVR period. [46][47][48][49][50] The developed prediction model for HCC has also been created to guide follow-up strategies. 51,52 It is noteworthy that the risk of HCC persists even after 10 years of viral eradication.…”
Section: Hccmentioning
confidence: 99%
“…[710] In addition, epidemiological studies suggested that DM confers a 2- to 3-fold increase in HCC risk in patients with CHC, regardless of whether the patient has undergone curative hepatectomy or antiviral therapy. [4,1014] Moreover, the development of HCC may be associated with diabetes duration and antidiabetic drug treatment. [15] …”
Section: Introductionmentioning
confidence: 99%